Error Analysis on Instiki's Students' Toeic Writing Simulation Test - Maria Osmunda Eawea Monny; Evelyn Angelita Pinondang Manurung (Journal on Education, 2024)
This study aims to find out the grammatical errors in their TOEIC writing simulation test. This is qualitative research that uses Surface Strategy Taxonomy (SST) to examine the errors. The participants of this study are 26 students of Class L – INSTIKI. The results of this study showed that after examining the data using SST based on the data were 3 errors found those are omission with 26 errors (81,3%), addition with 3 errors (9,4%), and misformation with 3 errors (9,4%). These 3 errors have each Sub Kind of Error (SKE), omission with 26 data consisting of missing “to be” with 10 data (38,5%), missing article “the” with 4 data (15,4%), preposition “of” with 2 data (7,7%)), preposition “on” with 2 data (7,7%)), missing pronoun “it” with 1 data (3,8%)), and wrong spelling with 7 data (26,9%)). In addition, there were 3 data consisting of wrong pronouns (redundancy) with 2 data (66,7%), and wrong spelling with 1 data (33,3%). The last one is misformation consisting of 3 data, the error where wrong verb-ing consists of 2 data (66,7%), and wrong verb 2 consists of 1 data (33,3%). The data above shows that omission still has the highest number of errors while addition and misformation share the same number of errors. The omission happened mostly on tenses for example Simple Present Tense, modal verbs, and prepositions. In addition, wrong spelling also still becomes a problem in writing.